UNDERSTANDING THE UN-PRESENT OF MANAGEMENT ACCOUNTING IN ACTION: AN ETHNOGRAPHY OF A BOTTLING WATER COMPANY - Eddy R.Rasyid (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2008)
This paper is about the un-present of accounting-in-action. The study reported here is significant as there is an argument that accounting studies are supplied with the emergence and existence of accounting practices. Meanwhile, accounting existence is not always the case. This paper presents a story from a field that the absence of management accounting practices is not technical but embedded in the cultural significance of the company studied. The absence is not viewed as the failure of the management as this study does not look for variables statistically responsible for the failure. Instead, this study is informed by Geertz interpretive anthropology as it attempts to make sense of that absence.Keywords: management accounting absence; organisational cultures; Geertz interpretive anthropology.